2010
DOI: 10.1088/0031-9155/55/9/008
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic stimulation of the spine: the role of tissues and their modelling

Abstract: Numerical modelling of magnetic stimulation in the spine is a scarce subject in the literature, although it has been gaining clinical acceptance. In the present work we present the results from a simplified computational model of the spine. The results indicate that it is necessary to use a numerical technique for solving the problem, which takes into account tissue dispersion and both dielectric properties (conductivity and permittivity), since a difference of 14% in the induced electric fields was found when… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Some earlier studies describe unsuccessful attempts to stimulate the descending motor tracts using EMS over the spinal enlargements in humans (Ugawa et al 1989), dogs (Machida et al 1992), and pigs (Konrad et al 1994). However, it has been recently reported that even though intervertebral discs, spines, cerebrospinal fluid, and tissue induce a shielding effect, this does not completely prevent access of the field into the cord tissue (Efthimiadis et al 2010). The failure of the spinal electromagnetic field to stimulate descending tracts could be due to a lower intensity of electromagnetic fields and different coil configurations used in the abovementioned studies.…”
Section: Ems Over Intact T2 Vertebrae Activates Synaptic Inputs To Lumentioning
confidence: 99%
“…Some earlier studies describe unsuccessful attempts to stimulate the descending motor tracts using EMS over the spinal enlargements in humans (Ugawa et al 1989), dogs (Machida et al 1992), and pigs (Konrad et al 1994). However, it has been recently reported that even though intervertebral discs, spines, cerebrospinal fluid, and tissue induce a shielding effect, this does not completely prevent access of the field into the cord tissue (Efthimiadis et al 2010). The failure of the spinal electromagnetic field to stimulate descending tracts could be due to a lower intensity of electromagnetic fields and different coil configurations used in the abovementioned studies.…”
Section: Ems Over Intact T2 Vertebrae Activates Synaptic Inputs To Lumentioning
confidence: 99%
“…Computational modeling studies suggest that epidural stimulation, as well as transcutaneous stimulation, activates cutaneous afferents of posterior roots (Ladenbauer, Minassian, Hofstoetter, Dimitrijevic, & Rattay, 2010; Rattay, Minassian, & Dimitrijevic, 2000). Studies examining spinal electromagnetic stimulation suggest that in addition to stimulating roots, SEMS may penetrate and directly stimulate spinal cord tissue through intervertebral disc space (Efthimiadis, Samaras, & Polyzoidis, 2010). Several studies examining epidural stimulation demonstrate that through recruitment of afferent inputs electric activation can in turn involve several spinal circuits and induce activation of spinal reflex circuits, motoneuronal excitability, and pattern generating networks (Minassian et al, 2007; Sayenko, Angeli, Harkema, Edgerton, & Gerasimenko, 2014; Hofstoetter et al., 2015).…”
Section: Discussionmentioning
confidence: 99%
“…For frequencies about 1 kHz, simulation studies have been conducted using a head resp. spine model [27,101], in order to decide whether the displacement current can be neglected. To the knowledge of the authors, there are at present no studies for higher frequencies, though further empirical and numerical research is necessary to determine the validity of the quasistatic regime in conductivity imaging.…”
Section: Approximations For Lower Frequenciesmentioning
confidence: 99%